Identifying the most valuable customers of a supermarket chain in Cyprus: A Customer Database Analysis Using RFM - Papantoniou, Andreas (2012)
The current study aims to illustrate the usefulness of the utilization of customer data into the retail industry and in particular to the supermarket sector. This piece of work tries to fill the gap in the literature regarding the application of database marketing techniques to real-life examples and also to be the starting point of more research related to the Cypriot retail context. The main objective of this study is to analyse the customer database of a supermarket chain based in Cyprus in order to segment their customers into homogeneous groups and then proceed to the identification of the most valuable customers. The RFM analysis was employed in order to segment the customer database and score each customer group according their Recency, Frequency and Monetary values. The findings suggest that the most valuable group of customers was consisted from 3657 customers. These customers represent more than the 34% of the total gross sales while they comprise more than 10% of the total cardholders. Also, a number of other interesting findings were also discussed, such as other valuable segments, middle-ranked segments and the least valuable customers.